Nahwu Learning Strategy Based on the Typology of Qaulan in the Qur’an: Integration of Linguistics and Qur’anic Communication Ethics - Eka Mahendra Putra; Fitrah Mujetaba (ZAD Al-Mufassirin, 2026)
This study aims to formulate a conceptual framework for Nahwu instruction based on the six qaulan typologies presented in the Qur’an. Methodologically, this research employs a qualitative library-based approach. Primary data consist of Qur’anic verses related to qaulan and authoritative tafsir works, while secondary data are drawn from the literature on Arabic linguistics and language pedagogy. The collected data were systematically selected, thematically classified, interpreted using a tafsīr mawḍū‘ī (thematic exegesis) approach, and synthesized into pedagogical framework for Nahwu instruction. The findings show that the six qaulan typologies_ qaulan sadīdan, balīghan, maysūran, layyinan, karīman, and ma‘rūfan_ can be operationalized as pedagogical principles emphasizing grammatical accuracy, meaningful communication, instructional simplification, constructive and gentle feedback, learner affirmation, and social relevance, respectively. The novelty lies in the development of a Qur’an-based pedagogical communication model for Nahwu instruction. Theoretically, it contributes to Arabic language pedagogy by positioning Qur’anic communication ethics as a foundational framework for a more humanistic, value-oriented, and communicative approach to teaching Arabic grammar.